EXERCISE TOLERANCE TEST: A COMPARISON BETWEEN TRUE POSITIVE AND FALSE POSITIVE TEST RESULTS - Faisal, Abdul Wajid Khan; Abid, Abdul Rehman; Azhar, Muhammad (Journal of Ayub Medical College Abbottabad, 2007)
Background: To study the factors which predetermine the coronary artery disease in patients having positive Exercise Tolerance Test (ETT) after comparing the ETT test results and coronary angiographic findings in true positive and false positive groups. Methods: This Cross-sectional study was conducted at Punjab Institute of Cardiology, Lahore from January 1, 2004 to December 31, 2004. All patients who had ETT done for chest pain diagnosis were studied. Patients were advised coronary angiography if ETT was positive for exercise induced ischaemia. One hundred and forty eight patients had coronary angiography done after positive ETT. Patients were divided into two groups depending upon the angiographic findings, i.e., true positive and false positive. Both groups were compared with each other. Results: Out of 148 patients, 126 (85.1%) patients had true positive ETT and 22 (14.9%) patients had false positive ETT. The mean age of patients in true positive group was 48.96ï‚±9.08 years and 50.9ï‚±7.85 years in false positive group. One hundred and eighteen (93.7%) male patients and 8 (6.3%) female patients had true positive ETT, whereas 14 (63.6%) males and 8 (36.4%) females had false positive ETT (p<0.0001). There was no statistically significant difference in the two groups in comparison of age and other conventional risk factors like diabetes mellitus, hypertension, smoking, family history and dyslipidemia. Abnormal resting ECG had a statistically significant difference between the groups (p<0.04), likewise is hypertensive haemodynamic response during ETT (p<0.003). The symptom limited ETT as compared to no symptoms during ETT also conferred a statistically significant difference between the groups (p<0.0001). Strongly positive ETT was also associated with true positive ETT (p<0.002). Amongst the vessels involved the most common was the LAD 113 (89.7%), followed by LCX 80 (63.5%) and the RCA 72 (57.1%). Most of the patients 51 (40.5%) had three vessel disease as compared to SVD 34 (27%). Conclusion: It can be concluded that amongst the patients who have positive ETT, females with abnormal resting ECG, who achieve target heart rate and have a hypertensive haemodynamic response with no symptoms are likely to have a false positive test result. Conversely male patients with normal resting ECG who do not achieve target heart rate, have a normotensive haemodynamic response and a strongly positive, symptom limited ETT are likely to have a true positive treadmill test result. Keywords: Exercise tolerance test, Coronary artery disease, Coronary angiography, true positive, false positive.